THE DEVELOPMENT OF THE CREATIVE LEADERSHIP BASED ON THE FOUR VUDDHI-DHAMMA OF SCHOOL ADMINISTRATORS IN CHA-UAT DISTRICT UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Jamjaratsrisiri , Saovapa; PhrakruSumethpariyatikul; Srisuwan , Kasama (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research article were: 1) to study the current conditions in the development of the creative leadership of school administrators in Cha-Uat District, Nakhon Si Thammarat Primary Educational Service Area Office 3, 2) to investigate the development of the creative leadership based on the Four Vuḍḍhi-Dhamma of school administrators in Cha-Uat District, Nakhon Si- Thammarat Primary Educational Service Area Office 3, and 3) to propose guidelines for the development of the creative leadership based on the Four Vuḍḍhi-Dhamma for school administrators in Cha-Uat District, Nakhon Si Thammarat Primary Educational Service Area Office 3. This is qualitative research that collected data by using in-depth interviews with 15 involved persons about the participation condition, 5 experts in guideline creation, and 7 experts by using focus group discussion to evaluate feasibility, suitability, and utility. Data were analyzed qualitatively using content analysis. The results showed that: 1) The current conditions in development of the creative leadership of school administrators in Cha-Uat district found that in terms of imagination, school administrators inspired and encouraged teamwork, providing teachers with opportunities to express their opinions and developing new innovations. However, obstacles included slow operations and a lack of clarity, leading to uncertainty and conflicts. Regarding flexibility, administrators listened to the opinions of personnel and were opened to change, resulting in creative development and a positive learning environment. However, challenges included delays in implementation, resistance, and a lack of support from school personnel. In terms of vision, administrators set clear and creative goals, ensuring a definite direction for operations while allowing school personnel to participate in achieving success. This fosters motivation and commitment among staff toward school development. Nevertheless, obstacles such as a lack of understanding among personnel, insufficient internal support, and limited resources hinder the full realization of the intended vision. In term of trust, administrators acknowledged differing viewpoints and promote fair organizational progress, leading to an improved working atmosphere. However, a lack of clarity sometimes caused confusion and uncertainty among staff. Concerning creativity, administrators emphasized skill and experienced enhancement among personnel while encouraging teamwork. This fostered openness to learning and continuous professional development. However, conflicts may arise due to resistance from personnel who opposed creative approaches. 2) The guidelines for the development of creative leadership based on Four Vuḍḍhi-Dhamma principles of school administrators in Cha-Uat district, under Nakhon Si Thammarat Primary Educational Service Area Office 3, These aspects included: Imagination, Flexibility, Vision, Trust, and Creativity. These elements were applied in conjunction with the Four Vuḍḍhi-Dhamma, which consisted of (1) Sappurisasam ̇seva (Associating with virtuous and wise individuals), (2) Saddhammassavana (Listening to and learning true wisdom), (3) Yonisomanasika ̅ra (Thoughtful and analytical reflection), (4) Dhamma ̅nudhamṭmapatipatti (Practicing the Dhamma in accordance with the Dhamma). 3) The proposed guideline for the development of the creative leadership based on the Four Vuḍḍhi-Dhamma for school administrators in Cha-Uat district was found to be feasible, appropriate, and beneficial.